2008
DOI: 10.3354/meps07604
|View full text |Cite
|
Sign up to set email alerts
|

Otolith chemistry of juvenile spotted seatrout Cynoscion nebulosus reflects local natal regions of coastal Mississippi, USA

Abstract: Early juvenile spotted seatrout Cynoscion nebulosus (n = 199) were collected during late summer and autumn 2001 from shoreline habitats within 9 coastal regions bordering Mississippi Sound in the north-central Gulf of Mexico to ascertain how well fish could be spatially classified based on otolith chemistry. Left otoliths were assayed for trace element:Ca ratios of Ba, Li, Mg, Mn and Sr, and right otoliths for δ 13 C and δ 18 O. Significant overall differences in otolith chemistry existed among the 9 regions; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
(20 reference statements)
0
23
1
1
Order By: Relevance
“…Spotted seatrout is the most popular recreational marine fish in the Gulf of Mexico (Stunz and McKee, 2006;James et al, 2007;Comyns et al, 2008) and is intensively managed by Texas Parks and Wildlife Department to maintain this resource (Anderson and Karel, 2009). However, in Texas there are concerns about population declines of adults (both size and number) that has prompted regionalized management and reduced harvest limits in south Texas.…”
Section: Discussionmentioning
confidence: 99%
“…Spotted seatrout is the most popular recreational marine fish in the Gulf of Mexico (Stunz and McKee, 2006;James et al, 2007;Comyns et al, 2008) and is intensively managed by Texas Parks and Wildlife Department to maintain this resource (Anderson and Karel, 2009). However, in Texas there are concerns about population declines of adults (both size and number) that has prompted regionalized management and reduced harvest limits in south Texas.…”
Section: Discussionmentioning
confidence: 99%
“…While the relative contribution of different stable isotope ratios (specifically d 15 N and d 13 C, and 87 Sr: 86 Sr) to discriminate freshwater fish among different locations has been examined (Dubé et al, 2005;Kennedy et al, 2005), the relative discriminatory power of a combined suite of element concentrations and stable isotope ratios has only been quantified for one fish species in the marine environment (Thorrold et al, 1998). This is surprising given that in recent years combinations of element concentrations and stable isotope ratios have proved popular as biogeochemical tags of fish (Comyns et al, 2008;Walther & Thorrold, 2008;Zeigler & Whitledge, 2011). Thorrold and coauthors (Thorrold et al, 1998) found that analysing d 13 C and d 18 O values in combination with Mg, Mn, Sr and Ba in otoliths increased the accuracy of assigning juvenile weakfish (Cynoscion regalis) to natal estuarine areas with up to a 38% improvement in classification of fish to their natal estuary.…”
Section: Introductionmentioning
confidence: 95%
“…Sr, Mn, Ba and Mg) in calcified structures (e.g. fish scales and otoliths) have provided biogeochemical tags of the spatial locations inhabited by fish (Thorrold et al, 1998;Comyns et al, 2008;Walther & Thorrold, 2008;Zeigler & Whitledge, 2011). Recent developments in the literature have revealed exciting new applications of biogeochemical tags over large spatial scales in the marine environment (MacKenzie et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in recent years biologists have explored stable isotope relationships to these variables and have found, for instance, that δ 15 N and δ 87 sr are enriched in fish moving from estuarine to deep water habitats, and δ 13 C is enriched in seagrass habitats (Hobson, 1999: 320-321;Nagelkerken and van der Velde, 2004 Hanson, Koenig, and Zdanowicz, 2004;Dorval et al, 2004;Kennedy et al, 2005;Martin and Thorrold, 2005;Surge and Walker, 2005;Comyns et al, 2008;Fodrie and Herzka, 2008;Fodrie et al, 2010;cf. Chittaro et al, 2005cf.…”
Section: Habitat Analysismentioning
confidence: 99%